Pattern of Severe Acute Maternal Morbidity in a Tertiary Care Institute - Kaur, Narinder; Aryal, Shreyashi (Journal of Lumbini Medical College, 2016)
Introduction: Maternal mortality traditionally has been the indicator of maternal health all over the world. More recently review of the cases of severe acute maternal morbidity (SAMM), also termed as "near miss obstetrics events", and has been found to be a useful supplementary indicator to investigate maternal health care. Cases of near miss are those in which women present with potentially fatal complication during pregnancy, delivery, or the puerperium and survive merely by chance or by good hospital care. This study was done with the objective to analyze cases of SAMM at Lumbini Medical College Teaching Hospital (LMCTH), Nepal. Methods: A retrospective study of all cases meeting the WHO criteria for SAMM, during May 2015, was done. Cases meeting the WHO eligibility criteria for near miss cases were included in the study. Medical record of such cases in past one year was reviewed. Their socio demographic variables, parity, gestational age, associated organ dysfunction, ICU and hospital stay, management, and fetal and maternal outcome were noted. Results: During the study period, there were total of 28 cases of SAMM and two maternal mortality out of 2735 live births. Thus rate of SAMM was 1.02%, and maternal mortality rate was 0.07%. Majority of patients were unbooked (n=18, 64.28%) and 10 (35.71%) were illiterate. Commonest causes for admission to ICU was hemorrhage (n=10, 35.71%) followed by hypertensive disorders (n=9, 32.06%), sepsis (n=2, 7.14%), and obstructed labour (n=2, 7.14%). Laparotomy was performed in six (21.42%) women, obstetric hysterectomy in four (14.28%), and pelvic devascularization in two (10.71%). Conclusion: SAMM is a useful adjunct to maternal mortality to assess maternal health care. Improving facility based care and prompt referral, education of primary health care (PHC) staff can be a short term measure to quickly reduce the number of maternal deaths. Facility based monitoring and reporting of SAMM outcome is an important step for scaling up such efforts. DOI: https://doi.org/10.22502/jlmc.v3i2.72 J. Lumbini. Med. Coll. Vol 3, No 2, July-Dec 2015, page: 45-49